An integrated marketing communications campaign for the Cohen Program - Serrano, Ruel Endaya (Animo Repository, 2012)
While massive industrialization has brought with it a host of conveniences for most people, it cannot be denied that it has also ushered in a wealth of other problems like pollution, wanton disregard for the environment, misuse of technology, and intensified competition for natural resources. However, the biggest impact that modernization has brought into the world is how it has greatly transformed the eating habits of todays people. Fuelled by the desire to keep pace with todays heady lifestyle, most people nowadays no longer have the time nor the discipline to properly care for their body. People instead prefer to eat easy-to-cook, instant meals that, while filling, dont provide the bodys nutritional requirement. Compounding matters is the sedentary lifestyle caused by the advent of personal computers, handheld game consoles, tablets and smart phones. Now, more than ever, millions of people are confronted with diseases caused by obesity/overweight, their freedom to enjoy and live life to the fullest shackled by this menacing disease. This P 6,897,370.30 campaign budget will utilize the most efficient media mix to communicate the Cohen Program as a viable, weight-loss program that uses science to make you look and feel good inside and out. Hence, the Big Idea is The science behind true beauty: A body that is healthy inside and out. The campaigns effectiveness will be gauged at the end through survey interviews, website and social media interaction and sales comparison.